Ecological assessment of tree species composition and diversity in Federal University Dutsin-Ma Take-off campus, Katsina State, Nigeria (Agriculture, Food, and Natural Resources Journal, 2025)
ABSTRACTThe study assessed tree species diversity in the Federal University Dutsin-Ma Take-off campus (FUDMA), Katsina state, Nigeria. Stratified random sampling was employed for the study, with the study area stratified into five different locations, and Plots of 20 x 20m were laid across sample sites. All trees within the plots were recorded with their Diameter at Breast Height (DBH) measured. One hundred and sixty one (161) individual trees belonging to seven (7) families were encountered in the study area. Azadirachta indica (RA = 48.447%) was the most abundant specie. Out of the recorded number of tree species, second gate, clinic, mosque and sport complex areas  had the highest number of trees, each having 46(29%), 35(22%), 31(19%), 30(19%) respectively, while senate building recorded the lowest number of tree species, having 19 (11%). The local status of tree species revealed that majority (33.33%) were abundant and 25% were threatened/endangered. The pooled mean for the DBH of the trees in the study area was 0.498m. The Shannon-Wienner and Simpson indices ranged between 0.468-1.778 and 0.238-0.809 respectively. The record of rare and threatened indigenous tree species in the study suggests that little attention had been given to regeneration and management of these species. The need to raise more seedlings especially for threatened and endangered species for both enrichment planting and increased afforestation of the campus is opined in this study. Likewise that existing tree species within the campus be further protected from various forms of threats.
Keywords: Tree species composition; Inventory; Relative abundance; Management